PENGARUH PENDEKATAN MODEL ELICITING ACTIVITIES (MEAS) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK - Hamidah . (Jurnal Edukasi dan Penelitian Matematika, 2020)
This study aims to describe theoretically whether learning with the Model Eliciting Activities (MEAs) approach can improve students' mathematical communication skills. This type of research is the study of literature on improving mathematical communication skills through the Model Eliciting Activities (MEAs) approach. This research method uses review articles, which use research results from various journals as an alternative to support the results of the research will be conducted. The data used were five journals which have the same research problem. Based on the results of the review articles can conclude that mathematical communication skills of students who learn with the Model Eliciting Activity (MEAs) approach is better than mathematical communication skills of students who study with conventional learning.Keywords— Model Eliciting Activities, MEAs, Mathematical Communication